Comparing Solo- and Co-Offending Female Sex Offenders on Variables of Pathology, Offense Characteristics, and Recidivism. (December 2019) - Miller, Holly A.; Marshall, Ethan A.
Due to the smaller proportion of female sex offenders (2%-12% of all sexual offenses) compared with male sex offenders, we know much less about these women to aid in the assessment, treatment, and prevention of their offending behavior compared with men. One promising distinction in female sex offender typology is solo-offending females versus females who offend with a male co-offender. The current study uses a sample of 225 incarcerated female sex offenders to compare solo and co-offending women on variables of psychopathology, criminal history, victim and offender information, and recidivism rates. Results indicate that solo offenders are more likely to have male, unrelated victims, score higher on dominance and aggression, and are more likely to generally recidivate. Solo versus co-offending status was not a significant predictor for sexual recidivism. Implications for assessment and treatment are discussed.